1969
DOI: 10.1002/bjs.1800561012
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of atrophic gastritis

Abstract: It is suggested that all gastric ulcers should be examined using a modern gastroscope with biopsy facilities before any decision is taken on management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Thus, of 12 patients who had multiple biopsies and four patients who had repeat biopsies, only one had more than a 1+ difference in inflammation from one biopsy to aniother, and in only one other was there significant difference in glandular atrophy. Similar findings were reported by Joske et al (1955), Williams et al (1958), Kirkpatrick et al (1969. Exceptions to this are said to occur in antral gastritis and the rare cases of multifocal gastritis.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, of 12 patients who had multiple biopsies and four patients who had repeat biopsies, only one had more than a 1+ difference in inflammation from one biopsy to aniother, and in only one other was there significant difference in glandular atrophy. Similar findings were reported by Joske et al (1955), Williams et al (1958), Kirkpatrick et al (1969. Exceptions to this are said to occur in antral gastritis and the rare cases of multifocal gastritis.…”
Section: Discussionsupporting
confidence: 87%
“…These diseases were first described in anecdotal reports. Population based surveys were carried out in the 1960s and 1970s [1][2][3][4] and it was demonstrated that NACG can progress to ACG. These studies also showed an association between ACG and the pathogenesis of gastric cancer and other gastric diseases.…”
mentioning
confidence: 99%